A critical realist inquiry in conducting interdisciplinary research: an analysis of LUCID examples - Nastar, Maryam; Boda, Chad S.; Olsson, Lennart (Ecology and society, 2018)
In recent years, a strong natural science hegemony has predominantly framed our understanding of sustainability challenges and, as a result, the production of solution strategies. In countering this, some academic centers have sought to promote interdisciplinary research, starting from the recognition that the scale and complexity of sustainability challenges necessitates a plurality of different social science perspectives to be incorporated in research. In this article, we analyze the process and outcomes of one of these centers, namely, the Lund University Centre of Excellence for Integration of the Social and Natural Dimensions of Sustainability (LUCID), maintaining a heavy emphasis on incorporating social sciences into interdisciplinary sustainability research from its inception. First, we identify and motivate the selection of a consistent set of criteria for evaluating interdisciplinary research processes and outcomes. Second, we apply these criteria in an analysis of a selection of scholarly work produced at LUCID. Third, we evaluate the impacts of LUCID’s institutional settings on the process of interdisciplinary research. Finally, we assess to what degree the outcomes of LUCID research have managed to produce the synthetic integrated knowledge required to analyze and address complex sustainability challenges. Although the LUCID work in aggregate represents a plurality of social science perspectives, our analysis suggests that a meaningful synthetic integration of knowledge was accomplished in cases where researchers employed retroductive logic and adhered to the principles of methodological pluralism. In highlighting the need to systematically incorporate these essential elements into the research process, we stress the importance of institutional settings in terms of finance, administration, and providing a conducive intellectual environment wherein authentic interdisciplinarity can emerge. Maintaining the kinds of horizontal and vertical institutional integration characteristic of such conducive settings, however, poses a major challenge in light of current trends, at least in Sweden, toward more compartmentalized, disciplinary university structures.